2002
DOI: 10.1175/1520-0485(2002)032<1838:ibtisa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Indonesian Seas and the Indian Ocean in Observations and Numerical Models*

Abstract: Recent measurements from six bottom-mounted gauges are used with numerical model results to study the exchange of water between the Indonesian seas and the Indian Ocean via the Lesser Sunda Islands known collectively as Nusa Tengarra. The observations are approximately three years in length, from late 1995 to early 1999, and include measurements of bottom pressure, temperature, and salinity. The locations of the gauges are at the boundaries of three straits connecting the southern Indonesian seas with the east… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 24 publications
5
57
0
Order By: Relevance
“…In the Indian Ocean, anomalous westerly winds occur at both semiannual and intraseasonal frequencies (Potemra et al 2002). The mechanisms underlying the forcing at these frequencies are fundamentally different: during the monsoon transition seasons, roughly in May and November, westerly wind anomalies over the central part of the Indian Ocean force a semiannual Kelvin wave, commonly referred to as the Wyrtki jet (Wyrtki 1973).…”
Section: Background a Wind Forcingmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Indian Ocean, anomalous westerly winds occur at both semiannual and intraseasonal frequencies (Potemra et al 2002). The mechanisms underlying the forcing at these frequencies are fundamentally different: during the monsoon transition seasons, roughly in May and November, westerly wind anomalies over the central part of the Indian Ocean force a semiannual Kelvin wave, commonly referred to as the Wyrtki jet (Wyrtki 1973).…”
Section: Background a Wind Forcingmentioning
confidence: 99%
“…1). Theoretical (Durland and Qiu 2003;Johnson and Garrett 2006) and modeling (Qiu et al 1999) studies have demonstrated that nearly all of the incoming intraseasonal Kelvin wave energy should enter Lombok Strait, but in situ observations have shown Kelvin wave energy in Ombai Strait (Molcard et al 2001;Potemra et al 2002;Sprintall et al 2009, hereafter S09) and a recent modeling effort by Qu et al (2008) demonstrated the same. Syamsudin et al (2004) used altimetric data to estimate that 56% of incoming semiannual Kelvin wave energy enters Lombok Strait, but the amount of intraseasonal Kelvin wave energy entering Lombok Strait has not been well quantified with observations.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The potential predictability of ocean dynamics in the proximity of the ITF has attracted considerable interest in recent years [Qiu et al, 1999;Chong et al, 2000;Potemra et al, 2002;Syamsudin et al, 2004;Wijffels and Meyers, 2004;Iskandar et al, 2005Iskandar et al, , 2006Yu and Potemra, 2006;Atmadipoera et al, 2009]. For example, Wijffels and Meyers [2004] explored observation-based temperature and sea level variability within the Indonesian seas and southeast Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%